Cell‐free DNA testing in the maternal blood in high‐risk pregnancies after first‐trimester combined screening. (9th February 2016) - Persico, Nicola; Boito, Simona; Ischia, Benedetta; Cordisco, Adalgisa; De Robertis, Valentina; Fabietti, Isabella; Periti, Enrico; Volpe, Paolo; Fedele, Luigi; Rembouskos, Georgios
Abstract: Objective: The objective of this study was to investigate a strategy for clinical implementation of cell‐free DNA (cfDNA) testing in high‐risk pregnancies after first‐trimester combined screening. Methods: In 259 singleton pregnancies undergoing invasive testing after first‐trimester combined screening, a maternal blood sample was sent to the laboratory Natera for cfDNA testing using a single‐nucleotide polymorphism‐based methodology. Results: The cfDNA test provided a result in 249 (96.1%) pregnancies and, among these, identified as being at high risk 35 of 36 cases of trisomy 21, 13 of 13 with trisomy 18, five of five with trisomy 13 and three of four with sex chromosome aneuploidies. A policy of performing an invasive test in women with a combined risk of ≥1 in 10 or NT ≥4 mm and offering cfDNA testing to the remaining cases would detect all cases of trisomy 21, 18 or 13, 80% of sex aneuploidies and 62.5% of other defects and would avoid an invasive procedure in 82.4% of euploid fetuses. Conclusion: In high‐risk pregnancies after combined screening, a policy of selecting a subgroup for invasive testing and another for cfDNA testing would substantially reduce the number of invasive procedures and retain the ability to diagnose most of the observed aneuploidies. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Cell‐free DNA testing in the maternal blood is a highly efficient method of screening for common fetal trisomies. What does this study add? In high‐risk patients, after first‐trimester combined screening, a policy of selecting a subgroup for invasive testing and another for cfDNA testing ensures that most trisomies are detected and allows to diagnose more than 60% of abnormalities that are not currently investigated by the cfDNA test.